Integrated role of social elements toward obesity in Malay community - Norizan, Abdul Ghani; Atif Amin, Baig; Saif, Ullah (AESS Publications, 2019)
The pervasiveness of obesity has been increasing drastically in Malaysia, and proved to be a serious health issue along with its effect on the economic growth of the country. Obesity pervasiveness is found to be higher in Malay community as compared to other ethnics or communities. Hence, the aim of this study is to investigate the role of social elements toward obesity in Malay community. A quantitative (cross-sectional) survey was conducted by using questionnaire. A total of 150 obese people from Malay community (age: 20-59 years) were included in the study through purposive sampling. Body mass index of all participants was measured under given guidelines for Asian people. Inferential statistics (Spearman Correlation) was used to obtain the objective of the study. Social elements such as feelings (low self-esteem), body image dissatisfaction, eating habits, physical activity, physical activity barriers and media influence were correlated with obesity. However, dieting behavior, health knowledge and religiosity were found insignificant. This pioneer study has explored the mechanism and role of social elements toward obesity, and providing a baseline data for future researches. It is hoped that the state and federal government could take proactive actions against obesity ratio to secure the health of Malay community, and to decrease financial cost which will also be beneficial for economic growth of the country.